Long-Term Outcome of Single-Session, Ultrasound-Guided, Radiofrequency Ablation for Symptomatic Small, Lower Limb, Venous Malformations. Issue 1 (13th July 2022) - Verhaeghe, Laurence; Labarque, Veerle; Vranckx, Jan; Fourneau, Inge; Pans, Steven; Maleux, Geert
Objectives: To analyze the long-term clinical outcome of percutaneous, ultrasound-guided radiofrequency ablation (RFA) of peripheral low-flow vascular malformations (VM). Materials & Methods: Adolescent patients presenting with symptomatic VMs and referred for percutaneous management using RFA between January 2010 and January 2015 were identified by a search in the institutional interventional radiology database. Clinical and radiological follow-up up to April 2021 was based on retrospective analysis of patients' electronic medical records and imaging files. This retrospective study was approved by the institutional ethics committee. Results: Four female patients (median age 16 years) presented with lower extremity pain, swelling and functional disability related to VM as confirmed by magnetic resonance imaging. Two patients underwent percutaneous sclerotherapy previously. Clinical follow-up (mean of 8, 5 years) showed complete and sustained resolution of the symptoms in all patients; in one patient a persistent decrease in muscular strength of the treated limb was noted. Conclusion: Percutaneous, ultrasound-guided RFA is relatively safe and efficient with durable symptom relief in the management of small, lower limb VMs in adolescent patients.